Effectiveness of Ultrasound on Gait and Range of Motion among Athletes with Achilles Tendinitis - A Narrative Review - Kiran, Gajendran; Shakthi, Manogaran; Suriya, Nedunchezhiyan; Vinodhkumar, Ramalingam; Jagatheesan, Alagesan; Prathap, Suganthirababu (INTI International University, 2024)
Background: Achilles tendinitis is a common condition among sports players. It is caused by repetitive action and overuse of the Achilles tendon, with clinical characteristics such as inflammation, increased pain, improper gait, and decreased range of motion in the ankle. The objective of this study is to identify the potential effects of therapeutic ultrasound and range of motion in athletes with Achilles tendinitis. Method: This review includes studies obtained from Google Scholar, PubMed, Cochrane, and ResearchGate databases. Therapeutic ultrasound is specifically examined in all the studies included in the analysis of gait and the range of motion of the ankle. A systematic narrative review form is used to analyze the studies that meet the present study criteria. In total, five studies were included: one pilot study, one case study, three randomized control trials, one experimental study, and two longitudinal studies. Conclusion: From this review, we conclude that therapeutic ultrasound was found to be effective in improving the participants’ gait and ankle range of motion following Achilles tendinitis.